Thermal Radiation Effect on MHD Flow and Heat Transfer Analysis of Williamson Nanofluid Past Over a Stretching Sheet With Constant Wall Temperature - Kho, Yap Bing; Abid, Hussanan; Muhammad Khairul Anuar, Mohamed; Norhafizah, Md Sarif; Zulkhibri, Ismail; Mohd Zuki, Salleh (IOP Publishing, 2017)
In this paper, the boundary layer flow of Williamson nanofluids past over a stretching sheet in the presence of thermal radiation effect is analyzed. Using similarity transformations, the governing equations are reduced to a set of nonlinear ordinary differential equations (ODEs). These equations are solved numerically by with shooting method. The effects of Williamson parameter, magnetic parameter, radiation parameter, Prandtl number on velocity, temperature and concentration fields are shown graphically and discussed. It is found that the rate of heat transfer is higher for Williamson nanofluid compared to the classical viscous fluid. Also, the comparisons with existing results are provided in the literature.